Ruthenium Nanoparticles for Catalytic Water Splitting. Issue 12 (31st May 2019) - Creus, Jordi; De Tovar, Jonathan; Romero, Nuria; García‐Antón, Jordi; Philippot, Karine; Bofill, Roger; Sala, Xavier
Abstract: Both global warming and limited fossil resources make the transition from fossil to solar fuels an urgent matter. In this regard, the splitting of water activated by sunlight is a sustainable and carbon‐free new energy conversion scheme able to produce efficient technological devices. The availability of appropriate catalysts is essential for the proper kinetics of the two key processes involved, namely, the oxygen evolution reaction (OER) and the hydrogen evolution reaction (HER). During the last decade, ruthenium nanoparticle derivatives have emerged as true potential substitutes for the state‐of‐the‐art platinum and iridium oxide species for the HER and OER, respectively. Thus, after a summary of the most common methods for catalyst benchmarking, this review covers the most significant developments of ruthenium‐based nanoparticles used as catalysts for the water‐splitting process. Furthermore, the key factors that govern the catalytic performance of these nanocatalysts are discussed in view of future research directions. Abstract : Breaking it down : Catalysts for the hydrogen and oxygen evolution reactions are key components of new sustainable energy conversion schemes based on water splitting and sunlight. This review covers the most significant developments in ruthenium‐based nanoparticles as catalysts for these processes, focusing on factors that govern their performance.